2008
DOI: 10.1007/s10979-007-9117-5
|View full text |Cite
|
Sign up to set email alerts
|

The psychological inventory of criminal thinking styles and level of service inventory-revised: Screening version as predictors of official and self-reported disciplinary infractions.

Abstract: A total of 159 male inmates screened with the Psychological Inventory of Criminal Thinking Styles (PICTS) and Level of Service Inventory-Revised: Screening Version (LSI-R:SV) were followed for a period of 24 months for evidence of disciplinary infractions (incident reports). Eighty-three of these inmates also furnished a self-report of disciplinary infractions occurring during the 24-month follow-up. The PICTS General Criminal Thinking (GCT) score and LSI-R:SV total score correlated with and accurately identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
49
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(53 citation statements)
references
References 24 publications
4
49
0
Order By: Relevance
“…Examination of the relationship between importation and deprivation characteristics and receipt of any type of disciplinary infraction, throughout one calendar year, revealed that an inmate's age at prison admission, gang affiliation status, number of received visits, and criminal offense conviction were significant predictors. Consistent with earlier research, which found that younger inmates engaged more frequently in misconduct behind bars (Griffin & Hepburn, 2006;McReynolds & Wasserman, 2008;Walters & Schlauch, 2008;Welsh et al, 2007;Wooldredge et al, 2001), younger inmates in the present study were also more likely to receive any type of disciplinary infraction. Race, educational level, and marital status were not statistically significant in either model.…”
Section: Discussionsupporting
confidence: 91%
“…Examination of the relationship between importation and deprivation characteristics and receipt of any type of disciplinary infraction, throughout one calendar year, revealed that an inmate's age at prison admission, gang affiliation status, number of received visits, and criminal offense conviction were significant predictors. Consistent with earlier research, which found that younger inmates engaged more frequently in misconduct behind bars (Griffin & Hepburn, 2006;McReynolds & Wasserman, 2008;Walters & Schlauch, 2008;Welsh et al, 2007;Wooldredge et al, 2001), younger inmates in the present study were also more likely to receive any type of disciplinary infraction. Race, educational level, and marital status were not statistically significant in either model.…”
Section: Discussionsupporting
confidence: 91%
“…Age has been predictive of criminal thinking in some studies (Mandracchia & Morgan, 2012;Palmer & Hollin, 2003;Walters, 2003;Walters, Frederick, & Schlauch, 2007) but not in others Walters & Schlauch, 2008). Race also has been used to predict criminal thinking, but produced mixed results.…”
mentioning
confidence: 99%
“…Some studies, however, have found no relationship between age and criminogenic cognitions in adult offenders. Walters and Schlauch (2008) found age to be uncorrelated with PICTS General Criminal Thinking (GCT) scores, and Mandracchia and Morgan (2010) found age to be unrelated to the three criminogenic cognitions styles on the Measure of Offender Thinking Styles (MOTS; i.e., control, cognitive immaturity, egocentrism). There appear to be no studies, however, in which age was found to be positively correlated with criminogenic cognitions.…”
mentioning
confidence: 99%